Research progress of CRISPR/Cas systems in nucleic acid detection of infectious diseases - Jinying Dong; Yuguang Du; Lei Zhou (iLabmed)
Abstract Infectious diseases are a serious threat to human health, and accurate, rapid and convenient early detection of pathogens is the first step of active treatment. Technologies that detect pathogens have advanced significantly because of the development of fundamental disciplines and the integration of multidisciplinary fields. Among these technologies, nucleic acid detection technology is preferred because of its rapid measurement, accuracy and high sensitivity. The CRISPR/Cas system, consisting of Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) and CRISPR‐associated (Cas), is an adaptive immune system that specifically recognizes, binds and cleaves exogenous invasive nucleic acids. The CRISPR/Cas system is widely found in bacteria and archaea. Researchers have developed nucleic acid detection technologies with single‐molecule sensitivity, single‐base precision specificity, portability and low cost based on the specific cleavage and trans‐cleavage activities of the CRISPR/Cas system. The next generation of in‐vitro diagnostics is shifting to nucleic acid technology because this technology shows promise in a wide range of applications in resource‐constrained environments. In this review, the development and mechanism of the CRISPR/Cas system are presented together with representative CRISPR/Cas applications in nucleic acid detection. Additionally, the review summarizes future perspectives and trends of the CRISPR/Cas system in nucleic acid detection.